The Minangkabau Interpretation of The Qur’an: Tradition and Characteristics of The Minangkabau Interpretation of The Qur’an - Halimatussa'diyah, Halimatussa'diyah; Ilyas, Deddy; Zulfikar, Eko (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This article examines the interpretation of the Quran in Minangkabau from the perspectives of the method of interpretation, interpretation techniques, and interpretation schools of thought. Exegesis of the Quran is one of the sciences that Urang Siak (students) must study in the surau. With a passion for the Quran, literature relating to the Quran was discovered, which is the product of scholars from Minangkabau. The literature extends from Mahmud Yunus' Tafsir al-Quran al-Karim to Hamka's Tafsir al-Azhar. This research is a library research using primary sources such as exegesis books by Minangkabau scholars, including Tafsir al-Quran al-Karim by Mahmud Yunus, Tafsir al-Azhar by Hamka, RisÄlat al-Qawl al-BayÄn by Sulaiman al-Rasuli, KitÄb TafsÄ«r al-BurhÄn by Abdul Karim Amrullah, and Tafsir al-Azhar by Hamka. The secondary sources include exegesis books and other relevant books. The research is phenomenological and employs a scientific approach to interpretation and a historical approach. The findings indicate that textual interpretation predominates over contextual interpretation. Textual interpretation can be separated into conventional textual interpretation and contemporary textual interpretation. The traditional textual perspective interprets the Quran literally, whereas the contemporary textual perspective employs rational thought as well. The tradition of Minangkabau scholars interpreting the Quran began in the early 19th century, and the Minangkabau interpretation of the Quran cannot be isolated from the influence of Egyptian scholars' interpretations, particularly Tafsr Jallain.Â